Biomassa do LCC: combate ao Aedes aegypti e investigação do potencial ansiolítico em zebrafish (Danio rerio) - Almeida, Mayara Oliveira de (2023)
Cashew Nut Shell Liquid (CNSL), the only known plant source of unsaturated phenolic monomers, is composed of: anacardic acid (AA), cardanol (CDN), cardol (CD) and 2-methylcardol (2MCD). CNSL has several important biological activities, including: larvicidal, in the fight against Aedes aegypti and anxiolytic, in the treatment of anxiety disorder. Dengue and chikungunya are constantly increasing in the number of cases in Brazil. Another disease that has been affecting a large part of the world's population is anxiety. This work involves the synthesis and characterization of organophosphate and pyridine compounds derived from LCC, in addition to the microencapsulation with citrus pectin, of CDN and CD, for subsequent evaluation of larvicidal activity. The work evaluated the cytotoxicity in macrophages of the synthesized compounds, and also evaluated the in vitro inhibitory potential against acetylcholinesterase (AChE) of the organophosphorothioate derivatives. This study also involves the study of the toxicity and anxiolytic potential of the compounds CDN, CD, AA, cardanol pyridinium (CDN-BrP) and di-substituted phosphorothioate cardol (CD-dPS) in adult Zebrafish (Danio rerio). Considering the larvicidal potential, the results showed that the CDN and CD microcapsules were obtained with yields above 72% and microencapsulation efficiency above 65%. CD-dPS presented LC50 = 0.8 ppm, four times more efficient than the commercial larvicide Temephos (LC50 = 3.2 ppm). This derivative presented a halo diameter (1.1 cm) closest to the Eserine control (1.5 cm), and, therefore, the most efficient both as a larvicide and as an AChE inhibitor. CD-dPS did not present toxicity in macrophage cells at any of the concentrations tested, as did CDN-BrP. Regarding the anxiolytic potential, the results showed that all compounds caused a sedative effect, decreased the locomotor activity of the fish and were not toxic up to 96h of analysis. Furthermore, they presented anxiolytic behavior at all doses tested, with emphasis on CDN, which was more efficient than DZP, with a percentage of permanence in the clear zone (%PZC) of 91.16%, followed by CD-dPS with %PZC of 86.50%. Regarding the structure-activity, the molecular docking study showed that the di-unsaturated CDN-BrP required a lower concentration to inhibit the GABAA receptor. The di-unsaturated CDN-BrP-GABA complex was the most stable, with a lower affinity energy value compared to DZP. These results suggest that CNSL derivatives are promising materials for use as larvicides and anxiolytics, since they are non-toxic and come from a renewable and low-cost source.